The long jump. (10th June 2014) - Martínez-del-Rio, Javier; Pérez-Valls, Miguel
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to help Ibero-American researchers identify the key challenges and benefits of moving to an Anglo-Saxon university for a period in their careers. Design/methodology/approach – This is a review of the insights provided by a number of prominent Ibero-American scholars based on the main experiences they have encountered. Findings – The paper analyzes three situations: a research visit, searching for a long-term position in North America (NA) and pursuing a PhD program in NA. The paper introduces some principles to succeed in these situations. Originality/value – The paper defines different strategies to take full advantage of a professional stage in an Anglo-Saxon/US university.